Enhanced activation of Mg ion-implanted GaN at decreasing annealing temperature by prolonging duration. (24th December 2020) - Nakashima, Takuya; Kano, Emi; Kataoka, Keita; Arai, Shigeo; Sakurai, Hideki; Narita, Tetsuo; Sierakowski, Kacper; Bockowski, Michal; Nagao, Masahiro; Suda, Jun; Kachi, Tetsu; Ikarashi, Nobuyuki
Abstract: Defect time-evolution was investigated in Mg ion-implanted GaN after annealing at 1573 K for an unprecedentedly long duration. Transmission electron microscopy directly revealed that annealing for over 30 min reduced defects inhibiting Mg activation, just like annealing at 1753 K for a short duration. The cathodoluminescence intensity of donor–acceptor pair originating from Mg acceptors increased as the duration increased, and the intensity after annealing for 60 min was higher than after short-duration annealing at 1753 K. These show the potential of lowering the annealing temperature by prolonging the duration, which would lead to practical annealing technology for Mg ion-implanted GaN.